2022
DOI: 10.2298/botserb2202209u
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and antioxidant activity of Trigonella cariensis seeds

Abstract: The genus Trigonella (Fabaceae) has been widely used for both culinary and clinical purposes since ancient times. The aim of this study was to investigate the chemical composition and in vitro antioxidant activities of Trigonella cariensis seeds for the first time. The seeds were collected in the province of Mersin, Turkey. Chemical analyses were performed using chromatographic methods. Fatty acid, tocopherol and sterol analyses were done on hexane extracts and amino acid and mineral analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Those results showed that major amino acids were determined as glutamic acid (3.79-4.82 % w/w), aspartic acid (2.65-3.31 % w/w), arginine (2.45-3.26 % w/w), leucine (1.67-2.09 % w/w), and lysine (1.63-1.95 % w/w) (14). In another study conducted by our group, the amino acid compositions of T. kotschyi, T. filipes and T. cilicica seeds were studied, and it was determined that the amounts of leucine, lysine, aspartic acid and glutamic acid in the seeds of all three species were higher than the other amino acids (8). As a result of amino acid analysis of T. strangulata seeds, it was found that the amounts of lysine (2482 mg/100 g), arginine (2244 mg/100 g), and leucine (2053 mg/100 g) were higher than other amino acids (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those results showed that major amino acids were determined as glutamic acid (3.79-4.82 % w/w), aspartic acid (2.65-3.31 % w/w), arginine (2.45-3.26 % w/w), leucine (1.67-2.09 % w/w), and lysine (1.63-1.95 % w/w) (14). In another study conducted by our group, the amino acid compositions of T. kotschyi, T. filipes and T. cilicica seeds were studied, and it was determined that the amounts of leucine, lysine, aspartic acid and glutamic acid in the seeds of all three species were higher than the other amino acids (8). As a result of amino acid analysis of T. strangulata seeds, it was found that the amounts of lysine (2482 mg/100 g), arginine (2244 mg/100 g), and leucine (2053 mg/100 g) were higher than other amino acids (9).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously conducted studies on the chemical compositions of some Trigonella species (T. kotschyi, T. filipes, T. cilicica, T. strangulata and T. rhytidocarpa) and their amino acid compositions have also been investigated (8)(9)(10). In this study, it was aimed to investigate, for the first time, the amino acid profile of three different Trigonella species (T. cylindracea Desv., T. mesopotamica Hub.-Mor.…”
Section: Introductionmentioning
confidence: 99%